Optimalisasi Peran KSM Desa Jamaras Dalam Penyuluhan PHBS Melalui Teknik Komunikasi Persuasif - Fitrananda, Charisma; Affandi, Nur Ratih Devi; Aulia, Salma Huda; Mustika, Febrianty Ajeng (Jurnal Pengabdian Masyarakat DEDIKASI, 2022)
Environmental health problems that exist in Jamaras Village, Jatihandap Village, Mandalajati District, Bandung City are one of the reasons for inaccurate communication, and make issues such as dengue fever, stunting children, lack of clean water and others occur because of uneven health information to the public. For several environmental health cases, the Non-Governmental Organization in Jamaras Village felt that it was not optimal to communicate to invite the community to maintain the cleanliness and health of the environment. Many people still do not want to participate in cleaning their environment, so dengue fever mosquitoes breed in various places. The purpose of this service is to provide training in effective persuasive communication techniques for KSM in counseling on Healthy Clean Lifestyles (PHBS). Partners in this service are the Jamaras Village Community Self-Help Group which contains youth groups, family welfare empowerment and the Boy Loves the Environment (Bocil). This mentoring activity is carried out by solving communication problems in the field with several solutions, providing materials on persuasive communication techniques and conducting practical counseling simulations.